Development of Student Worksheets in Mathematics Learning of Grade XII Statistics Materials with Project Based Learning Model - Meisy Wijayanti Mokoagow; Anetha L. F. Tilaar; Ontang Manurung (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Mathematics education in Indonesia, particularly in high schools, faces significant challenges in improving students' understanding of abstract concepts, especially in statistics. The lack of practical application and the focus on memorization of formulas hinder students' ability to relate mathematical concepts to real-life situations. To address these challenges, Project-Based Learning (PjBL) is proposed as an effective approach that engages students in real-world projects, encouraging active participation, critical thinking, and the application of mathematical concepts. This study employs the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop a Student Worksheet (LKPD) based on PjBL for teaching statistics in class XII at SMK Kesehatan Bulawan. The development process includes analyzing the curriculum, student characteristics, and learning goals, followed by designing, validating, and revising the LKPD. The product is then implemented in a small group trial and evaluated for its validity, practicality, and effectiveness through expert validation, practical questionnaires, and student learning tests. The LKPD received very high validity, with expert validation scores of 95% for content and 90% for design, resulting in an average score of 92.5%. Practicality assessments showed a 91.5% average, indicating the LKPD was easy to use by both teachers and students. The effectiveness of the LKPD was confirmed by an 80% average student achievement rate, with 80% of students meeting the KKM (Minimum Completeness Criteria). The developed LKPD based on PjBL is highly valid, practical, and effective for improving students' understanding of statistics, making it a suitable tool for enhancing mathematics education in SMK.